Implementation In House Training in Making Learning Media for Early Childhood Teacher - Rima Dewi Kartini; Nita Priyanti (Journal of Childhood Development, 2024)
In the context of early childhood education, the use of learning media has a very important role in supporting an effective learning process. Therefore, this research aims to explore the application of in-house training in creating learning media for early childhood teachers. The research method used is qualitative by collecting data through interviews, observation and documentation at Bina Keluarga, West Metro District. The research results show that in-house training makes a positive contribution in increasing teachers' understanding of the role and benefits of learning media as well as improving the quality of their skills in creating learning media that suits the needs of young children. However, there are challenges related to the timing of training and evaluation which is less structured. Therefore, it is recommended that training accommodate all teacher skill needs, a structured evaluation system is implemented to monitor teacher understanding, and teaching staff in the school environment continue to improve their professional competence